Kehidupan Remaja dalam Perkembangan Pariwisata di Desa Ped, Kecamatan Nusa Penida, Bali - Padmi Sami Antari, Ni Luh; Wiasti, Ni Made; Suwena, I Wayan (Sunari Penjor : Journal of Anthropology, 2021)
This research discusses the lives of adolescents both before and after the development of tourism in Ped Village, Nusa Penida District. As for the problems that will be discussed in this research are (1) how the youth lifestyle in the development of tourism in Ped Village, Nusa Penida District and (2) what are the implications of youth lifestyle on their social and cultural life in Ped Village, Nusa Penida District. This research is a qualitative study using personality theory and cultural theory as a basis for answering the two problems. The results of this study reveal that the lifestyle of adolescents in Ped Villages before and after the development of tourism, namely changes in behavior and objects consumed in daily activities. There are implications for the lifestyle of adolescents, namely the existence of economic and socio-cultural changes in the lives of adolescents in the Ped Village.